Trends in pneumonectomy for treatment of small-cell lung cancer. (November 2020) - Zhao, Jasmine; Nguyen, Alexandra; Ding, Li; David, Elizabeth A; Atay, Scott M; Wightman, Sean C; McFadden, P Michael; Kim, Anthony W
Background: According to practice guidelines, patients with clinical stage T1–2 node-negative small-cell lung cancer are candidates for surgical resection. However, the role of pneumonectomy in small-cell lung cancer patients is not well understood. The objective of this study was to assess the extent to which pneumonectomy is used and to evaluate the survival implications for small-cell lung cancer patients who underwent pneumonectomy. Methods: A total of 106 small-cell lung cancer patients who underwent pneumonectomy between 2006 and 2016 and met the study criteria were identified in the National Cancer Database. Demographics and treatment regimens are described, and overall survival was assessed using Kaplan-Meier and log-rank tests. Results: The most common treatment was surgery with adjuvant chemotherapy, followed by surgery only and surgery with neoadjuvant therapy. The 5-year overall survival for the entire cohort after pneumonectomy was 23%. In subgroup analysis, the 5-year overall survival was 30% for guideline-concordant clinical stage I patients and 28% for clinical stage II/III patients who underwent pneumonectomy. There was no statistical difference in survival according to pathologic N disease. Patients with a right-sided pneumonectomy had higher mortality than patients with a left-sided pneumonectomy. Conclusions: This study suggests a role for pneumonectomy in clinical stage I and potentially some clinical stage II and III small-cell lung cancer patients. Right-sided pneumonectomy is associated with higher mortality and should be approached with caution. Despite declining trends over the past decades, pneumonectomy is still an effective treatment that is able to achieve acceptable survival outcomes.